Comparación de las Estrategias de Regeneración Natural entre los Bosques Primarios y Secundarios en las zonas bajas del Atlántico Costarricense. - Leiva-Sanabria, Jorge (Instituto Tecnológico de Costa Rica, 2001)
For two general forest types: secondary growth forest and adjacent old growth forest, was compared: the tree species spatial distribution, floristic composition, affinity, species diversity and the proportions of the tree species regeneration in the understory without representative individuals in the canopy. The succession process in the analyzed secondary growth forests was related with the proximity of the old growth forest seed source, as well as the general implications of these comparisons to the forest management of the second growth and old growth forests of this region of the country. The second growth forest Lindero El Peje was the most similar to the old growth forests in terms of diversity, floristic composition and common species dominance afinnity. The analyzed secondary growth forests had an average proportion of species without representative individuals in the canopy of 0.76 0.056, while the old growth forest had an average proportion of 0.66 0.037. The secondary growth forests had a great proportion of dispersed species from outside forest of the plots, that coincided with the succession process where a tree community will eventually substitute the present in the canopy. Probably, this proportion was higher in the second growth forests because of the most homogeneous environmental conditions, while in the old growth forests the proportion was smaller because of the most heterogeneous establishment conditions. The major implications that these general proportions have in the eventual case of management of these forests are: a. This great proportion of canopy absent regeneration in the secondary growth forests, could not responded favorably to the gaps opening, because of its shade tolerant behavior. b. The understory regeneration has been considered only on isolated cases, in the sustainable forest management planning of the second and old growth forests in Costa Rica.
Proyecto de Graduación (Bachillerato en Ingeniería Forestal). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Forestal, 2001.
Keywords: Zonas tropicales; Manejo de bosques; Composición florística; Clima; Vegetación; Muestreo; Suelo